lac repressor blocks in vivo transcription of lac control region DNA. - Sellitti, M A (1987)
Transcription of the Escherichia coli lac repressor gene (lacI) in vivo produces monocistronic mRNAs with discrete 3' ends in the lac control region, although the DNA sequence of this region does not specify a strong termination signal of the traditional form. Direct analysis of lac transcripts was used to show that the DNA sequence alone does not provide the signal to end the repressor mRNA and to establish that of the proteins with specific binding sites on control region DNA only the lac repressor has a striking effect on the continuity of lacI gene transcription. RNAs with 3' ends in the control region sequence are major mRNA species produced from a repressor-bound template, reflecting as much as a 50-fold increase over their levels in the repressor's absence. Repressor binding to the operator thus has a dual function. In addition to blocking initiation of transcription from the lacZ promoter, repressor serves as a termination factor by setting the length of its own transcript and separating lacI and lacZYA into two distinct transcription units.